2021
DOI: 10.1038/s41375-021-01346-7
|View full text |Cite
|
Sign up to set email alerts
|

The RNA-binding protein IGF2BP3 is critical for MLL-AF4-mediated leukemogenesis

Abstract: Despite recent advances in therapeutic approaches, patients with MLL-rearranged leukemia still have poor outcomes. Here, we find that the RNA-binding protein IGF2BP3, which is overexpressed in MLL-translocated leukemia, strongly amplifies MLL-Af4-mediated leukemogenesis. Deletion of Igf2bp3 significantly increases the survival of mice with MLL-Af4-driven leukemia and greatly attenuates disease, with a minimal impact on baseline hematopoiesis. At the cellular level, MLL-Af4 leukemia-initiating cells require Igf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 75 publications
1
41
0
Order By: Relevance
“…Thus, IGF2BP3 is an attractive therapeutic target as demonstrated in this study and other researches. 43 In addition, we found that DNA mutations regulated extensive AASEs primarily through trans-regulatory mode and most trans-sQTLs belonged to missense mutations. Especially, we noticed that the hotspot mutation of TP53 would affect a wild range of alternative splicing of other genes in LUAD, which is difficult to understand at first glance.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Thus, IGF2BP3 is an attractive therapeutic target as demonstrated in this study and other researches. 43 In addition, we found that DNA mutations regulated extensive AASEs primarily through trans-regulatory mode and most trans-sQTLs belonged to missense mutations. Especially, we noticed that the hotspot mutation of TP53 would affect a wild range of alternative splicing of other genes in LUAD, which is difficult to understand at first glance.…”
Section: Discussionmentioning
confidence: 79%
“…Thus, IGF2BP3 is an attractive therapeutic target as demonstrated in this study and other researches. 43 …”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, IGF2BP3 interacts with RCC2 mRNA and stabilizes the expression of modified m 6 A RNA. 47,77 Taken together, these studies uncover the similar functional roles of different m 6 A modifiers (writers, erasers, and readers) via totally distinct mechanisms.…”
Section: Roles and Mechanisms Of M 6 A In Amlmentioning
confidence: 74%
“…These results suggested that future studies should focus more on the expression of gene subtypes or different transcripts rather than the overall expression level of genes. As a member of the IGF2BPs family, a series of studies have shown that IGF2BP3 is associated with the proliferation and metastasis of colon cancer [ 41 ], bladder cancer [ 42 ], gastric cancer [ 43 ], and other malignant tumours [ 44 , 45 ]. In addition, IGF2BP3 can also participate in the regulation of mRNA stability and translation through the recognition of m 6 A sites, such as MYC, CDK6, or Cyclin D1 [ 41 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%